Src‐dependent phosphorylation of μ‐opioid receptor at Tyr336 modulates opiate withdrawal - Zhang, Lei; Kibaly, Cherkaouia; Wang, Yu‐Jun; Xu, Chi; Song, Kyu Young; McGarrah, Patrick W; Loh, Horace H; Liu, Jing‐Gen; Law, Ping‐Yee (EMBO molecular medicine, 2017)
Opiate withdrawal/negative reinforcement has been implicated as one of the mechanisms for the progression from impulsive to compulsive drug use. Increase in the intracellular cAMP level and protein kinase A (PKA) activities within the neurocircuitry of addiction has been a leading hypothesis for opiate addiction. This increase requires the phosphorylation of μ‐opioid receptor (MOR) at Tyr 336 by Src after prolonged opiate treatment in vitro . Here, we report that the Src‐mediated MOR phosphorylation at Tyr 336 is a prerequisite for opiate withdrawal in mice. We observed the recruitment of Src in the vicinity of MOR and an increase in phosphorylated Tyr 336 (pY336) levels during naloxone‐precipitated withdrawal. The intracerebroventricular or stereotaxic injection of a Src inhibitor (AZD0530), or Src shRNA viruses attenuated pY336 levels, and several somatic withdrawal signs. This was also observed in Fyn −/− mice. The stereotaxic injection of wild‐type MOR, but not mutant (Y336F) MOR, lentiviruses into the locus coeruleus of MOR −/− mice restored somatic withdrawal jumping. Regulating pY336 levels during withdrawal might be a future target for drug development to prevent opiate addictive behaviors. Synopsis The μ‐opioid receptor (MOR) non‐canonical signaling pathway involves its phosphorylation at Tyr 336 by Src kinase within the MOR signal complex. The focal event of MOR Y 336 phosphorylation may be the key for adenylyl cyclase superactivation during the withdrawal/negative stage of opiate addiction. The phosphorylation levels of MOR Y 336 and Src Y416 increased during naloxone‐precipitated withdrawal in wild‐type mice. The intracerebroventricular or stereotaxic injection of a Src inhibitor (AZD0530), or Src shRNA viruses reduced pMOR Y 336 and pSrc Y416 levels, and several somatic withdrawal signs. Increases of pMOR Y 336 levels as well as some somatic withdrawal signs after naloxone‐precipitated withdrawal were not observed in Fyn −/− mice. The stereotaxic injection of wild‐type MOR lentiviruses into the locus coeruleus of MOR −/− mice restored somatic withdrawal jumping and wet dog shaking. The stereotaxic injection of the phosphorylation‐deficient mutant (Y336F) MOR, in which the mutation of Tyr 336 to Phe blocks Src‐mediated phosphorylation, attenuated naloxone‐precipitated withdrawal. Graphical Abstract The μ‐opioid receptor (MOR) non‐canonical signaling pathway involves its phosphorylation at Tyr 336 by Src kinase within the MOR signal complex. The focal event of MOR Y336 phosphorylation may be the key for adenylyl cyclase superactivation during the withdrawal/negative stage of opiate addiction.